Application of the Dijkstra Method in the Geographic Information System of the Nearest School Route Based on Android - Muhammad Syahputra Novelan; Dian Kurnia; Rizky Putro Nugroho Dwi Cahyo (INFOKUM, 2021)
Klambir V Kebon Village, Hamparan Perak District, Deli Serdang Regency is one of the villages that has a variety of and quality education locations. To advance the world of education in the village of Klambir V, it is necessary to have information media that can take advantage of android smartphones. Therefore we need a geographic information system that produces information for directions to the closest location from where you live to an Android-based school. One of the methods used to find the closest route is the Djikstra method. This method can complete the search for the shortest path from an origin vertex to a destination vertex in a weighted graph. The result of this system is that with the application of finding the shortest path, the process of finding the nearest school can be accessed more quickly and with accurate information. The Djikstra algorithm used in the process of finding the shortest path is very helpful and easy to understand by the author. Distance information at each point becomes clearer and can manage the time in the school search process.